Mathematics of mobile application in basic education for teaching children of fundamental I 1st to 3rd year (Research, Society and Development, 2016)
Many students who complete primary education have difficulties in learning math. Given the affinity that children have with electronics, it is interesting to develop applications that support learning. The objective of this article is to present a case study of software development to support the teaching of mathematics. Technology has enabled the possibility of introducing programming principles in the curricula to encourage students to create their own educational digital games. In the present work, it was developed, in Java ™ programming language, a mobile application for the Android ™ platform, that teaches math in a fun way through gamification elements. This application includes practical exercises of the four mathematical basic operations that are demonstrated through interactive images, animations and educational games.